Determinants and knowledge of men on obstetric danger signs: A community-based cross-sectional study in Debretabor, Ethiopia - Abeba Belay Ayalew; Marta Berta; Mihretu Molla; Habtamu Biazin Kebede (Elsevier, 2024)
Introduction: Obstetrics danger signs are the major health problems and cause of mortality among women in developing countries including Ethiopia. To make an informed decision man should know the danger signs of pregnancy, childbirth, and postpartum and be able to act when they occur. In this regard, the role of men as decision-makers cannot be overlooked. However, studies regarding knowledge and associated factors of obstetric danger signs were limited in Ethiopia. Objectives: This study aimed to assess knowledge and associated factors towards obstetric danger signs among men in Debretabor town North West, Ethiopia. Method: A community-based cross-sectional study was conducted among 609 participants from February 1 -March 30/2021 in Debre Tabor town. A cluster sampling procedure was used. Data were collected through a pretested semi-structured interviewer-administered questionnaire. Data were entered into Epi data version 4.6 and exported into SPSS version 25 for analysis. All variables with a p-value < 0.2 in the Bivariable analysis were entered into multivariable logistic regression analysis. The statistically significant association of variables was determined based on the Adjusted Odds ratio with a 95 % confidence interval and p-value < 0.05. Results: Six hundred and nine men were interviewed which made a response rate of 96.9 %. Men's knowledge of obstetrics danger signs was (44.8 %). In logistic regression analysis the wife's previous obstetrics danger sign (AOR = 5.34,95 %CI (3.49-8.16), diploma and above education (AOR = 7.27, 95 %CI (2.13-8.83), wife's antenatal care (AOR = 2.44, 95 % CI (1.29-4.64), wives gave birth at the hospital (AOR = 4.38, 95 %CI 1.69-11.31) and health development army leader (AOR = 3.86, 95 %CI (1.38-10.75) were associated with knowledge level. Conclusion: In this study men's knowledge of obstetrics danger signs was low. Husband's education, place of delivery, and antenatal care have a great role in improving men's knowledge. The government and stakeholders should give due emphasis to creating awareness and health education about obstetrics danger signs in this particular community.